Consumer Innovativeness Model of Indonesian Young People in Adopting Electronic Products - Nasution, Reza Ashari; Astuti, Novika Candra (ASEAN Marketing Journal, 2021)
It is important for marketers to understand how innovators respond to the introduction of new products. This paper investigates consumer innovativeness (CI) from meta-analysis study as suggested by Nasution and Garnida [2011] and examines the simultaneous impacts of CI on new product adoption. Nasution and Garnida [2010] proposed three different perspectives in conceptualizing the CI model. First, the generalist stream that represents a generalized personality trait that engenders consumers to adopt new product. Second, the particularist stream that focuses on product adoption behavior within a specific domain of interest. Third, the integrator perspective that proposes to integrate these two streams by putting domain-specific innovativeness as a mediating factor in relationship between general innovativeness trait and new product adoption.A structural equation model is used to test hypotheses using empirical data from 607 respondents in electronic products adoption. The result shows that the integrator perspective provides the best model in representing the empirical data. The finding of the integrator perspective reveals that domain specific CI mediates the relationship between general innovativeness trait and new product adoption. Specifically, subjective knowledge and hedonic idea shopping enhances the actuality of new products.The findings provide an explanation to the less than consistent relationship between consumer innovativeness and new product adoption. However, a single research context of electronic products and student sample may become one of the limitations and future studies needed to replicate the perspective of CI in different research contexts for greater generalizability and the use of non-student sample. The findings have implications for the innovation adoption theory, for managers involved in the introduction of new products, and for future research on innovation adoption.